The Organisational and Information Systems of Rolls Royce to Succeed the 150 seater Replacement Project - Hatta, Muhammad (2007)
The market value for a 150 seater engine in the next 20 years will be worth approximately US $185 billion. However, the Rolls Royce market share is only around 5% in the current market. In addition, the company is also facing some operations and organisational issues.